PEMBERIAN PEMAHAMAN MENGENAI DAGUSIBU DI JORONG CARUAK KECAMATAN IV KOTO KABUPATEN AGAM - Hilmarni Hilmarni; Intan Suweni; Nurasiah Wahid (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The development of science and technology in pharmacy, especially drug production, has led to more types and quantities of drugs in circulation. This condition has had various positive and negative impacts. The positive impact is increasinG the number of people who care about health by going to health service places, while the negative impact that may occur is an error in the use of drugs. The DAGUSIBU activity (Dapatkan, Gunakan,Simpan, Buang) is one of the health promotions of the Indonesian Pharmacists Association (IAI) in an effort to create the GKSO Movement (Conscious Family Movement) as a concrete step to improve the quality of life of the community to achieve the highest health status. The purpose of this dedication is to see knowledge and provide understanding of DAGUSIBU to the people of Jorong Caruak, IV Koto District, Agam Regency. The service was carried out by filling out the questionnaire before and after giving directly material. From 35 respondents, there was a lack of understanding data about DAGUSIBU before education (56.42%), while the public understanding after getting education of DAGUSIBU was very good (93.14%).